The Contribution of Applying Drama Techniques in Teaching English - Febriantara, I Nyoman Deva (Jurnal Ilmu Multidisiplin Indonesia, 2024)
Ttudy discussed the contribution or effect offered by the use of drama as a technique in teaching in the EFL classroom, whether it is a good or bad contribution. Through a literature review, several scientific articles were used in this study, of which selected scientific journals from 2000 to 2020 which were obtained from official sources or educational websites. First, the data collection technique is carried out by analyzing the related studies/articles that have been done previously. Second, the data that has been obtained from several scientific articles containing the same research is managed by paraphrasing technique in order to obtain valid data. The result in this study shows that the use of drama has a good contribution in improving language skills, motivation and good character building for students but also drama cannot be applied to all student characters